Change management for library technologists a LITA guide - McAllister, Courtney, 1984- (LITA guides., 2019)
This guide is designed to equip practitioners with the strategies they need to master interpersonal and technical interdependencies. Learn how to socialize technological changes within your library, assess the core competencies and comfort levels of colleagues, direct reports, and end users, and methodically optimize both library technologies.